ŞOCURILE EXTERNE ŞI EFECTELE DE INTERDEPENDENŢĂ A ŢĂRILOR EUROPEI CENTRALE ŞI DE EST - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2007)
Living in a globalized world fool of interdependence, it is impossible for countries to act without taking into account the other neighboring states, as each action taken has an impact on the others. Considering these circumstances, the new phenomenon of contagion appears and influences different countries no matter the level of their development. Each country should take appropriate strategies in order to prevent the effects of the contagion and react with flexibility and quick adaptation to the changes.